Design, modelling, and testing of a vibration energy harvester using a novel half-wave mechanical rectification. (1st December 2020) - Mi, Jia; Li, Qiaofeng; Liu, Mingyi; Li, Xiaofan; Zuo, Lei
Graphical abstract: Highlights: A novel half-wave mechanical rectification for vibration energy harvesting. Nonlinear dynamics to understand the proposed system and optimize the parameters. The power output of the proposed system can double that of full-wave rectification. Bench and treadmill tests to verify the model and evaluate the system performance. The specific power of can reach 0.4 W/kg under a 4.8 km/h walking speed. Abstract: Portable and wearable electric devices are an important part of our life and the energy supply is critical for their functions. Energy harvesting from human motion is a promising solution to provide the energy supply. This paper presents the design, modeling and testing of a vibration energy harvester using a novel half-wave mechanical rectification to enhance the performance of suspended energy harvesting backpack. The proposed half-wave mechanical rectification mechanism uses one set of rack-pinion and a one-way clutch that converts bidirectional vertical oscillation into unidirectional rotation of the generator with nonlinear inertia. As validated by both modelling and bench tests, the proposed half-wave mechanical rectification-based energy harvesting system can obtain about twofold average output power as the previous full-wave mechanical rectification system in the desired dominant excitation frequency and also maintains larger output power in the target frequency range. The influences of external resistance, human walking speed, and payload mass are also studied to comprehensively characterize the performance and robustness of the proposed design. Treadmill tests on different human subjects demonstrate an average power range of 3.3–5.1 W under a walking speed of 4.8 km/h (3 mph) with a 13.6 kg (30 lbs.) payload. Experimental results indicate that the proposed suspended energy harvesting backpack could continuously generate an amount of electricity suitable for powering portable and wearable electronic devices, which can be applied to the military, field workers, outdoor enthusiasts and disaster relief scenarios.